Endophytic Fungi Isolated from Baccharis linearis and Echinopsis chiloensis with Antifungal Activity against Botrytis cinerea - Paulo Castro; Rodolfo Parada; Carlos Corrial; Leonora Mendoza; Milena Cotoras (Journal of Fungi, 2022)
Botrytis cinerea is one of the most important phytopathogens in agriculture worldwide, infecting economically important crops. The main control of this fungus is by synthetic fungicides, causing the selection of resistant isolates. Compounds produced by endophytic fungi have been shown to have antifungal activity against this pathogen and can be used as an alternative to synthetic fungicides. The aim of this work was to isolate endophytic fungi from Chilean foothills in the Metropolitan Region. Ten fungi were isolated from Echinopsis chiloensis and Baccharis linearis, however, only two isolates inhibited the mycelial growth of B. cinerea by antibiosis and were identified as Epicoccum sp. and Pleosporales sp. Extracts at 200 mg L−1 from Epicoccum sp. and Pleosporales sp. showed antifungal activity against B. cinerea of 54.6 and 44.6% respectively. Active compounds in the Epicoccum sp. extracts were mainly alkaloids and phenolic compounds; meanwhile, in the Pleosporales sp. extracts, terpenes and/or saponins were responsible for the antifungal activity.